Optimal plane for nerve sparing total mesorectal excision, immunohistological study and 3D reconstruction: an embryological study. (December 2013) - Bertrand, M. M.; Alsaid, B.; Droupy, S.; Benoit, G.; Prudhomme, M.
Abstract Aim Genito‐urinary complications are frequent after rectal surgery and are often due to nerve damage. The relationship between the pelvic nerves and surgical planes are unclear. The aim of the study was to determine the relationship between the inferior hypogastric plexus and the fascia of the lateral pelvic wall and between Denonvilliers' fascia and the efferent branches of the inferior hypogastric plexus. Method Computer‐assisted anatomical dissection was used. Serial histological sections were made from six human foetuses and a male adult. Sections were stained with haematoxylin and eosin, Masson's trichrome and immunostainings. The sections were then digitalized and reconstructed in three dimensions. Results The inferior hypogastric plexus was situated in a virtual space between the fascia propria of the rectum and the fascia on the upper surface of the levator ani. During the lateral dissection, the optimal surgical plane is the plane of the fascia propria of the rectum. We located Denonvilliers' fascia in three dimensions. It plays the role of a protective sheet for the neurovascular bundle. The optimal plane for nerve preservation is situated behind Denonvilliers' fascia. Conclusion This study has enabled a clear visualization of the optimal planes to perform total mesorectal excision while ensuring nerve preservation. Three‐dimensional visualization clearly helps to bridge the gap between histological examination and the findings of surgery.